Gender, gender identification and perceived gender discrimination: An examination of mediating processes in China. Issue 8 (16th November 2015) - Foley, Sharon; Ngo, Hang-yue; Loi, Raymond; Zheng, Xiaoming
Abstract : Purpose: – The purpose of this paper is to examine the effects of gender and strength of gender identification on employees' perception of gender discrimination. It also explores whether gender comparison and perceived gender bias against women act as mediators in the above relationships. It aims to advance the understanding of the processes leading to individual's perception of gender discrimination in the Chinese workplace. Design/methodology/approach: – Data were collected from 362 workers via an employee survey in three large companies in China. The human resource staff helped us to distribute a self-administered questionnaire to the employees, and the authors assured them of confidentiality and protected their anonymity. To test the hypotheses, the authors employed structural equation modeling. The authors first conducted confirmatory factor analysis on the measurement model, and then the authors estimated three nested structural models to test the mediating hypotheses. Findings: – The results reveal that gender and strength of gender identification are related to perceived gender discrimination. The authors further found that gender comparison and perceived gender bias against women partially mediated the relationship between gender and perceived gender discrimination, while gender comparison fully mediated the relationship between strength of gender identification and perceived gender discrimination. Practical implications: – The study helps managers understand why and how their subordinates form perceptions of gender discrimination. Given the findings, they should be aware of the importance of gender identity, gender comparison, and gender bias in organizational practices in affecting such perceptions. Originality/value: – This study is the first exploration of the complex relationships among gender, gender identification, gender comparison, perceived gender bias against women, and perceived gender discrimination. It shows the salient role of gender comparison and gender bias against women in shaping employees' perceptions of gender discrimination, apart from the direct effects of gender and strength of gender identification.